Global Monitoring Report 2010 : The MDGs after the Crisis - World Bank; International Monetary Fund (World Bank, 2012)
What is the human cost of the global economic crisis? How many people will the crisis prevent from escaping poverty, and how many will remain hungry? How many more infants will die? Are children being pulled out of schools, not getting the education they need to become more productive adults and making it virtually impossible to reach 100 percent completion in primary education by 2015? What are the gender dimensions of the impacts? These are some of the questions as the global economy comes out of the worst recession since the great depression. The questions do not have immediate answers, partly because the data to assess development outcomes are incomplete and collected infrequently but also because impacts can take several years to emerge. For example, deteriorating health and nutrition today could lead to higher mortality rates in subsequent years. Lower investments will hamper future progress in sanitation and water supply. Fewer children in school will lower completion rates in later years. And household incomes that fall far below the poverty line will delay escapes from poverty. This report uses indirect evidence to assess the impact of the crisis on several indicators, including the number of people who will not escape poverty, the increase in infant mortality, the number of children who will be denied education, and the increase in discrimination against women. Based on that assessment, the report identifies key policies necessary for the developing countries, donors, and the international financial institutions (IFIs) to reestablish progress toward the Millennium Development Goals (MDGs).